Socially Responsible International Business 2019
DOI: 10.4337/9781788114127.00009
|View full text |Cite
|
Sign up to set email alerts
|

An overview of social responsibility dimensions in international business

Abstract: This chapter aims at taking stock of business-responsibility-related studies in international business (IB) research. Key features of this literature review include (1) a broad search strategy capturing both positive and negative aspects of responsibility, (2) not imposing any constraints on the time period, and (3) extending the search to all IB journals included in the Web of Science database. By incorporating both responsible and irresponsible behavior in the search strategy, we are able to provide a holist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 280 publications
(309 reference statements)
0
17
0
Order By: Relevance
“…This is all the more important because responsible behavior is not binary. Sinkovics et al (2019) suggest thinking of such behavior as a continuum between two extremes; that is, maliciously irresponsible firm behavior and behavior that is responsible in every possible way. In this paper, we take this suggestion one step further and argue that organizations' activities can be mapped onto two continua.…”
Section: Introductionmentioning
confidence: 99%
“…This is all the more important because responsible behavior is not binary. Sinkovics et al (2019) suggest thinking of such behavior as a continuum between two extremes; that is, maliciously irresponsible firm behavior and behavior that is responsible in every possible way. In this paper, we take this suggestion one step further and argue that organizations' activities can be mapped onto two continua.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, we adopt a systematic review approach (Luo et al , 2019), focusing on published articles in key IB journals. As in Sinkovics et al (2019), our population of IB journals includes 16 IB journals identified by Tüselmann et al (2016), namely, Journal of World Business , Journal of International Business Studies , International Business Review , European Journal of International Management , Asia Pacific Journal of Management , Asia Pacific Business Review , Journal of International Management , Management and Organization Review , Management International Review , critical perspectives on international business , Thunderbird International Business Review , Global Strategy Journal , Multinational Business Review , Journal of East West Business , Transnational Corporations and Journal of Asia Pacific Business . In addition, we include the new Journal of International Business Policy .…”
Section: Research On Inequality In International Business: a Reviewmentioning
confidence: 99%
“…This is because these topics are multifaceted and different fields may have different approaches and underlying assumptions. As Sinkovics et al (2019) point out, literature reviews can provide a good starting point for scholars new to an area of research, or inspiration for new research ideas for scholars already familiar with the topic. The rest of the paper is structured as follows.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this paper is to investigate how different academic fields engage with the topic of social value creation in the context of multinational enterprises (MNEs). While recent studies attempt to provide a more clear-cut conceptualisation of social value (Sinkovics et al, 2015;Sinkovics et al, 2014), for the purposes of this review we will adopt a very general definition to capture a broader range of scholarly engagement with the topic (Sinkovics et al, 2019). More specifically, we regard any positive societal or environmental outcome that arises from the activities of MNEs as social value.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation